COLLECTIVE LEARNING IN A LEARNING ORGANIZATION: GROWING TEAM LEARNING CULTURE TO SURVIVE AND DEVELOP - Adi Suryani (JURNAL SOSIAL HUMANIORA (JSH), 2012)
A learning organization has a deep culture of learning. It is constantlyencourage its member to learn. This learning activity is not only for adapting tothe rapid changing of its internal and external environment, but also forgrowing. The effort of a learning organization to create a conducive learningclimate can be indicated by training its members. Working towards a learningorganization has both its strengths and drawbacks. The strengths are it canimprove the organization performance and organization survival. However,learning too rapid can lead to learning stress. Moreover it can lead to harshinternal competition.